1999
DOI: 10.1007/s005860050153
|View full text |Cite
|
Sign up to set email alerts
|

Is there a rational basis for post-surgical lifting restrictions? 1. Current understanding

Abstract: IntroductionAfter surgery it is a common practice to prescribe lifting restrictions. These seem to be based on a premise that the spine is weaker and thus subject to re-injury when there has been some disruption of the functional spinal motion unit (FSU) due to surgery. Re-injury is not, however, often reported in the literature. More often a failure of fusion is reported [3, 6, 12, 23, 27,72,79].Recurrent low back pain (LBP) or other impairments may exist after back surgery in up to 50% of operated patients [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
2
13
0
1
Order By: Relevance
“…Previous surveys highlighted variations with respect to recommendations regarding return to work ranging from 1–16 weeks [ 7 , 20 ]. Similarly, a study by Magnusson et al [ 21 ] into restrictions on lifting revealed obvious differences in recommendations. Magnusson et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous surveys highlighted variations with respect to recommendations regarding return to work ranging from 1–16 weeks [ 7 , 20 ]. Similarly, a study by Magnusson et al [ 21 ] into restrictions on lifting revealed obvious differences in recommendations. Magnusson et al .…”
Section: Discussionmentioning
confidence: 95%
“…Magnusson et al . [ 21 ] were unable to identify any evidence in the literature to support such restrictions, even when mechanical factors were considered [ 22 ]. Our paper now adds evidence of a notable discordance between post-operative restrictions on sitting and recommendations about return to sedentary work or driving.…”
Section: Discussionmentioning
confidence: 99%
“…for sitting, driving, or sedentary work. Magnusson et al [42] found similar inconsistency and lack of scientific rationale in advice about lifting, with recommendations about work demonstrating even greater variability [33,40]. Lack of advice, or inconsistent and contradictory advice, makes patients uncertain what they should or should not do postoperatively, which is likely to increase anxiety and inhibit their rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the suggested additions/revisions to the RNLE by the aforementioned studies (Hidalgo et al, 1997; Jager & Luttmann, 1999; Stambough et al, 1995), Magnusson et al suggested adding the factor of “stiffness change” as yet another multiplier. The recommendation was to be added to accommodate “post-surgery workers” who typically have restricted lifting capabilities (Magnusson, Pope, Wilder, Szpalski, & Spratt, 1999). The rationale for this addition was described in a subsequent paper (Pope, Magnusson, Wilder, Goel, & Spratt, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The recommendation was to be added to accommodate “post-surgery workers” who typically have restricted lifting capabilities (Magnusson, Pope, Wilder, Szpalski, & Spratt, 1999). The rationale for this addition was described in a subsequent paper (Pope, Magnusson, Wilder, Goel, & Spratt, 1999). To our knowledge, all the suggested revisions to the RNLE model have not been validated.…”
Section: Resultsmentioning
confidence: 99%